2017
DOI: 10.1590/1981-863720170002000063332
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, alcohol consumption and oral cancer among healthcare academics

Abstract: Objective To evaluate if dental students with the habit of smoking exhibit alterations in the epithelial cells of the cheek mucosa on the nuclear area (NA), cytoplasmic area (CA) or in the nucleus/cytoplasm ratio (NA/CA), when compared to non-smokers. Methods This is a descriptive, experimental study using a control group. The sample comprised 40 dental undergraduates (20 smokers and 20 nonsmokers). Individuals who smoked at least 5 or 6 cigarettes a day were deemed to be smokers, while non-smokers were those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…We found that mean cytoplasmic area is significantly higher in control group when compared to tobacco users group. Similar findings were observed by (Parmar et al, 2010;Babuta et al, 2014;Santos et al, 2017;). Decrease in the cytoplasmic area of smokeless tobacco users may be due to the fact that there is a close contact between the smokeless tobacco and oral mucosa.…”
Section: Discussionsupporting
confidence: 90%
“…We found that mean cytoplasmic area is significantly higher in control group when compared to tobacco users group. Similar findings were observed by (Parmar et al, 2010;Babuta et al, 2014;Santos et al, 2017;). Decrease in the cytoplasmic area of smokeless tobacco users may be due to the fact that there is a close contact between the smokeless tobacco and oral mucosa.…”
Section: Discussionsupporting
confidence: 90%